Determinación del incremento de peso de la tilapia roja oreochromis sp utilizando diferentes densidades de siembra - Aguilar Ochoa, Walter Llasmany (2012)
This research was conducted in the province of El Oro, Santa Rosa Canton, on the farm owned by Jorge Barco, which is located via Puerto Jeli. In the present study analyzed the weight gain under different planting densities, the same had three objectives: 1. Set the appropriate density for growing tilapia, 2. To compare the survival of tilapia at different stocking densities, 3. Set the weight gain of tilapia at different stocking densities. This work started from planting of young fish, having a duration of four months, with its inception in February and ending in May 2011. The red tilapia fingerlings were bought at the farm of Mr. Barco and were planted at densities of: 3 Alv/m2, 6 and 9 Alv/m2 Alv/m2 feeding began and ended with a balanced 32% protein , the frequency was twice daily, morning (8:00) and afternoon (14:00), how food was the "bowling". Regarding the results, the pool No. 1 had a slight superiority over the other two, in terms of survival, it was 97%, considered very good, the conversion in the pool No 1 was 0 , 6, and this is relatively good.